A method for preparing large-particle hemihydrate gypsum by acid decomposition of high-impurity phosphate ore

By controlling the sulfate ion concentration and adding modifiers, the high-impact phosphate acid is directly decrystallized to prepare large-grained semi-water gypsum, which solves the problem of long process flow, high energy consumption and difficult to prepare large-grained semi-water gypsum in the existing technology, and achieves the effects of process simplification, cost reduction and filtration efficiency improvement.

CN116812962BActive Publication Date: 2025-04-18WUHAN INST OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310763973.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-04-18
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

When converting phosphogypsum into semi-water gypsum, the process flow is long, the energy consumption is high, and it is difficult to directly prepare large-grain semi-water gypsum in high-impact phosphate ores, resulting in low filtration efficiency and easy blockage of the filter cloth.

Method used

By controlling the sulfate ion concentration and adding modifiers, the high-impact phosphate acid is directly decrystallized to prepare large-grained semi-water gypsum, avoiding the transformation process of dihydrate gypsum.

Benefits of technology

It significantly shortens the process flow, reduces production costs, improves filtration efficiency, solves the problem of filter cloth clogging, and allows high-impact phosphate ore to be used in the direct crystallization process of semi-water gypsum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004306138980000011
    Figure HDA0004306138980000011
  • Figure HDA0004306138980000012
    Figure HDA0004306138980000012
  • Figure HDA0004306138980000013
    Figure HDA0004306138980000013
Patent Text Reader

Abstract

The invention belongs to the technical field of semi-hydrated phosphogypsum production, and discloses a method for preparing large-particle semi-hydrated gypsum by acid hydrolysis of high-impurity phosphate ore. The method comprises the following steps: 1) mixing phosphate rock powder with phosphoric acid for pre-dissolution to obtain a pre-dissolved slurry; 2) continuing to add phosphate rock powder to the pre-dissolved slurry for acid hydrolysis to obtain an acid hydrolysis slurry; 3) adding a modifier and concentrated sulfuric acid to the acid hydrolysis slurry for crystallization to obtain a semi-hydrated slurry; 4) performing solid-liquid separation on the semi-hydrated slurry to obtain large-particle semi-hydrated gypsum. The invention directly crystallizes high-impurity phosphate ore by acid hydrolysis to prepare semi-hydrated gypsum, and increases the particle size of the semi-hydrated gypsum by controlling the sulfate ion concentration and adding a modifier, effectively solving the problems of low filtration rate and blockage of semi-hydrated filter cloth in the production process, so that high-impurity phosphate ore can also be used in the direct crystallization process of semi-hydrated gypsum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semi-hydrated phosphogypsum production, and in particular relates to a method for preparing large-particle semi-hydrated gypsum by acid hydrolysis of high-impurity phosphate ore. Background Art

[0002] In the traditional wet phosphoric acid production process, almost all solid impurities such as acid insolubles enter the phosphogypsum (dihydrate gypsum), which makes the gypsum of low quality and difficult to comprehensively utilize. The storage and treatment of phosphogypsum not only occupies a large amount of land, but also easily pollutes water bodies, soil, vegetation, and the atmospheric environment. The huge investment and management and operation costs of phosphogypsum yards, as well as the increasing environmental protection and safety pressures, have seriously restricted the survival and development of phosphate fertilizer companies. Hemihydrate gypsum has a wider range of applications, such as polishing powder, paper filler, gas desiccant, and medical plaster bandages. It is also used in metallurgy and agriculture. Therefore, the factory hopes to convert phosphogypsum into hemihydrate gypsum to achieve the utilization of gypsum while reducing environmental pollution.

[0003] In response to the demand for converting phosphogypsum into semi-hydrated gypsum, Chinese patent CN113148968A discloses a method for producing α-semi-hydrated gypsum by wet phosphorus processing. The method first acidifies phosphate rock to obtain dihydrated gypsum slurry, and then crystallizes the dihydrated gypsum to obtain α-type semi-hydrated gypsum. This method solves the problem of converting phosphogypsum into semi-hydrated gypsum, but the process is long and the crystallization needs to be carried out at a higher temperature, and the energy consumption and time cost are not advantageous. Therefore, if it is possible to directly generate whiskers of semi-hydrated gypsum without crystallization of dihydrated gypsum during the production process, it will significantly shorten the process and reduce costs, which is more conducive to industrial production.

[0004] In the actual production process, the technical bottleneck of the direct crystallization process of semi-hydrated gypsum is that the crystallization process is difficult to control and the crystal size is small, which leads to low filtration efficiency in the subsequent filtration process, easy clogging of the filter cloth, and affects the continuous operation of the system; high impurity content in the raw phosphate rock will further aggravate the above problems. In the paper "Development and Use of Semi-hydrated-Dihydrate Phosphate Ore Evaluation Device" published by China Wuhuan Engineering Co., Ltd. in June 2020, it was proposed that the semi-hydrate process has high requirements for raw phosphate ore, and the impurity content requirements are Al2O3+Fe2O3≤2.3%, MgO≤1.0%, but most of the domestic phosphate ores cannot meet this standard.

[0005] 93% of my country's phosphate rock is of medium and low grade with high impurity content. A major challenge we are facing now is to break through the technical bottleneck of the direct crystallization process of hemihydrate gypsum while making use of medium and low grade phosphate rock with high impurity content to make the technology universal. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore in view of the shortcomings of the prior art. The method directly crystallizes the hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore, increases the particle size of the hemihydrate gypsum by controlling the sulfate ion concentration and adding a modifier, and effectively solves the problems of low filtration rate and clogging of hemihydrate filter cloth in the production process.

[0007] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore, comprising the following steps:

[0008] 1) mixing phosphate rock powder and phosphoric acid, controlling the temperature for pre-dissolution, and obtaining a pre-dissolved slurry;

[0009] 2) continuing to add phosphate rock powder to the pre-dissolved slurry, controlling the temperature for acid hydrolysis, and obtaining an acid hydrolysis slurry;

[0010] 3) adding a modifier to the acid hydrolysis slurry, and then adding concentrated sulfuric acid, controlling the temperature for crystallization, and obtaining a semi-aqueous slurry;

[0011] 4) The semi-hydrated slurry is subjected to solid-liquid separation, the liquid phase is crude acid, and the solid phase is washed and dried to obtain large-particle semi-hydrated gypsum.

[0012] In the above scheme, the particle size of the phosphate rock powder is ≤100 mesh, the P2O5 content of the phosphate rock powder is 28.5-30%, the MgO content is 1-2%, and the total content of Fe2O3 and Al2O3 is 3-5%.

[0013] In the above scheme, the mass concentration of the phosphoric acid is 33-38% calculated as P2O5.

[0014] In the above scheme, the mass ratio of phosphate rock powder to phosphoric acid added in step 1) is 1:(20-30).

[0015] In the above scheme, in step 1), the sulfate ion concentration in the liquid phase is controlled to be 1-2%.

[0016] In the above scheme, the pre-dissolution temperature is 80-85°C, and the pre-dissolution time is 0.5-1.0h.

[0017] In the above scheme, the mass ratio of phosphate rock powder to phosphoric acid added in step 2) is 1:(2.5-4).

[0018] In the above scheme, in step 2), the sulfate ion concentration in the liquid phase is controlled to be 2-5%.

[0019] In the above scheme, the acid hydrolysis temperature is 85-90°C and the acid hydrolysis time is 3-5h.

[0020] In the above scheme, the modifier is one or more of N-ethylacetamide and acrylamide.

[0021] In the above scheme, the concentration of the modifier in the acid hydrolysis slurry is 40-160 ppm.

[0022] In the above scheme, in step 3), the sulfate ion concentration in the liquid phase is controlled to be 4-10%.

[0023] In the above scheme, the crystallization temperature is 85-90°C and the crystallization time is 3-5h.

[0024] In the above solution, the particle size of the large-particle hemihydrate gypsum is 40-80 μm.

[0025] In the above scheme, the mass concentration of P2O5 in the crude acid is 40-45%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1) On the one hand, the present invention accelerates the dissolution and acid hydrolysis of phosphate rock by controlling the sulfate concentration. At the same time, calcium ions in the mineral powder and sulfate ions form calcium sulfate, which provides a similar effect as crystal seeds and increases the particle size of hemihydrate gypsum. On the other hand, a modifier is added during the crystallization process to aggregate small particles of hemihydrate gypsum to form a larger whole. In the process of forming larger particles, the pore size is also increased, making filtration easier, effectively solving the problems of low filtration rate and blockage of hemihydrate filter cloth in the production process, so that high-impurity phosphate rock can also be used in the direct crystallization process of hemihydrate gypsum.

[0028] 2) The present invention directly crystallizes phosphate rock by acid hydrolysis to prepare hemihydrate gypsum, and does not require a crystallization process, which can significantly shorten the process and reduce costs; the concentrated sulfuric acid added during the preparation process can increase the temperature of the reaction system and reduce the energy required for the reaction, thereby further saving production costs; the crude acid obtained after crystallization has the characteristics of high phosphoric acid concentration and good acid quality compared to the crude acid obtained by the dihydrate method, which is conducive to the subsequent production of finished acid; in summary, the present invention has a good application prospect in actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD pattern of the large-particle hemihydrate gypsum prepared in Example 1.

[0030] Figure 2 This is the SEM image of the large-particle hemihydrate gypsum prepared in Example 1.

[0031] Figure 3 This is the XRD pattern of the large-particle hemihydrate gypsum prepared in Example 3.

[0032] Figure 4This is the SEM image of the large-particle hemihydrate gypsum prepared in Example 3.

[0033] Figure 5 This is the SEM image of the semi-hydrated gypsum prepared in Comparative Example 1.

[0034] Figure 6 This is the SEM image of the semi-hydrated gypsum prepared in Comparative Example 2.

[0035] Figure 7 This is the SEM image of the semi-hydrated gypsum prepared in Comparative Example 3. DETAILED DESCRIPTION

[0036] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0037] In the following examples, two kinds of medium and low grade phosphate ores with high impurity content were selected, and the main parameters are shown in the table below.

[0038] Table 1

[0039] Particle size <![CDATA[P2O5 content]]> <![CDATA[Fe2O3 content]]> <![CDATA[Al2O3 content]]> MgO content Phosphate Ore A 100 mesh 28.7 1.394 2.657 1.112 Phosphate rock B 100 mesh 28.6 0.457 1.739 1.977

[0040] Example 1

[0041] A method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore, comprising the following steps:

[0042] 1) Take 1200g of phosphoric acid with a P2O5 concentration of 38% and heat it to 85°C, add 50g of phosphate rock powder A, and the sulfate ion concentration in the liquid phase is detected to be 1.8%, pre-dissolve for 0.5h to obtain a pre-dissolved slurry;

[0043] 2) The pre-dissolved slurry was heated to 90° C., 320 g of phosphate rock powder A was added, and the sulfate ion concentration in the liquid phase was detected to be 3%, and acid hydrolysis was performed. The sulfate ion concentration in the liquid phase was monitored in real time. When the concentration began to decrease, concentrated sulfuric acid was added to maintain the sulfate ion concentration at 4%. The acid hydrolysis was performed for a total of 3 hours to obtain an acid hydrolysis slurry;

[0044] 3) adding a mixed modifier consisting of acrylamide and N-ethylacetamide in a mass ratio of 1:4 to the acid hydrolysis slurry to make the concentration of the modifier in the acid hydrolysis slurry be 120 ppm, then adding concentrated sulfuric acid to maintain the sulfate ion concentration in the liquid phase at 7%, and crystallizing at 85° C. for 3 hours to obtain a semi-aqueous slurry;

[0045] 4) The semi-hydrated slurry is subjected to solid-liquid separation, the liquid phase is crude acid with a P2O5 mass concentration of 43.8%, and the solid phase is washed and dried to obtain large-particle semi-hydrated gypsum.

[0046] Figure 1This is the XRD diagram of the large-particle hemihydrate gypsum prepared in this example. It can be seen from the figure that the diffraction peak position and relative intensity are basically consistent with the hemihydrate gypsum standard card, proving that the product is hemihydrate gypsum.

[0047] Figure 2 This is a SEM image of the large-particle hemihydrate gypsum prepared in this example. It can be seen from the image that the particle size of the hemihydrate gypsum is 55-80 μm. Under the dual effects of the modifier and sulfate ions, the small particles of hemihydrate gypsum are agglomerated to form an integral large-particle hemihydrate gypsum, and the large particle structure contains pores, which is conducive to filtration.

[0048] Example 2

[0049] 1) Take 1200g of phosphoric acid with a P2O5 concentration of 38% and heat it to 82°C, add 50g of phosphate rock powder B, and the sulfate ion concentration in the liquid phase is detected to be 1.8%, pre-dissolve for 1h to obtain a pre-dissolved slurry;

[0050] 2) The pre-dissolved slurry was heated to 85° C., 400 g of phosphate rock powder B was added, and the sulfate ion concentration in the liquid phase was detected to be 2.5%. Acid hydrolysis was performed, and the sulfate ion concentration in the liquid phase was monitored in real time. When the concentration began to decrease, concentrated sulfuric acid was added to maintain the sulfate ion concentration at 3.5%. The acid hydrolysis was performed for a total of 4 hours to obtain an acid hydrolysis slurry;

[0051] 3) adding a mixed modifier consisting of acrylamide and N-ethylacetamide in a mass ratio of 1:4 to the acid hydrolysis slurry to make the concentration of the modifier in the acid hydrolysis slurry be 150 ppm, then adding concentrated sulfuric acid to maintain the sulfate ion concentration in the liquid phase at 9%, and crystallizing at 90° C. for 3 h to obtain a semi-aqueous slurry;

[0052] 4) The semi-hydrated slurry is subjected to solid-liquid separation, the liquid phase is crude acid with a P2O5 mass concentration of 44.1%, and the solid phase is washed and dried to obtain large-particle semi-hydrated gypsum, with a particle size of 55-70 μm.

[0053] Example 3

[0054] 1) Take 1200g of phosphoric acid with a P2O5 concentration of 35% and heat it to 85°C, add 60g of phosphate rock powder A, and the sulfate ion concentration in the liquid phase is detected to be 1.5%, pre-dissolve for 0.5h to obtain a pre-dissolved slurry;

[0055] 2) The pre-dissolved slurry was heated to 90° C., 300 g of phosphate rock powder A was added, and the sulfate ion concentration in the liquid phase was detected to be 3.5%. Acid hydrolysis was performed, and the sulfate ion concentration in the liquid phase was monitored in real time. Concentrated sulfuric acid was added in the later stage of acid hydrolysis to maintain the sulfate ion concentration at 2%. The acid hydrolysis was performed for a total of 5 hours to obtain an acid hydrolysis slurry;

[0056] 3) adding a modifier N-ethylacetamide to the acid hydrolysis slurry to make the concentration of the modifier in the acid hydrolysis slurry 80 ppm, then adding concentrated sulfuric acid to maintain the sulfate ion concentration in the liquid phase at 5%, and crystallizing at 90° C. for 4 hours to obtain a semi-aqueous slurry;

[0057] 4) The semi-hydrated slurry is subjected to solid-liquid separation, the liquid phase is crude acid with a P2O5 mass concentration of 43.6%, and the solid phase is washed and dried to obtain large-particle semi-hydrated gypsum.

[0058] Figure 3 This is the XRD diagram of the large-particle hemihydrate gypsum prepared in this example. It can be seen from the figure that although there are a certain amount of impurity peaks, this is due to the fact that some impurities in the mineral powder enter the hemihydrate gypsum during hemihydrate crystallization. The main diffraction peak position and relative intensity are basically consistent with the hemihydrate gypsum standard card, proving that the product is hemihydrate gypsum.

[0059] Figure 4 This is a SEM image of the large-particle hemihydrate gypsum prepared in this example. It can be seen from the image that the particle size of the hemihydrate gypsum is 40-60 μm. Under the dual effects of the modifier and sulfate ions, the small particles of hemihydrate gypsum are agglomerated to form an integral large-particle hemihydrate gypsum, and the large particle structure contains pores, which is conducive to filtration.

[0060] Example 4

[0061] 1) Take 1200g of phosphoric acid with a P2O5 concentration of 33% and heat it to 80°C, add 40g of phosphate rock powder B, and the sulfate ion concentration in the liquid phase is 2% after detection, pre-dissolve for 1h to obtain a pre-dissolved slurry;

[0062] 2) The pre-dissolved slurry was heated to 85° C., 400 g of phosphate rock powder B was added, and the sulfate ion concentration in the liquid phase was detected to be 2%. Acid hydrolysis was performed, and the sulfate ion concentration in the liquid phase was monitored in real time. When the concentration began to decrease, concentrated sulfuric acid was added to maintain the sulfate ion concentration at 5%. The acid hydrolysis was performed for a total of 4 hours to obtain an acid hydrolysis slurry;

[0063] 3) adding acrylamide as a modifier to the acid hydrolysis slurry to a concentration of 40 ppm in the acid hydrolysis slurry, then adding concentrated sulfuric acid to maintain the sulfate ion concentration in the liquid phase at 8%, and crystallizing at 90° C. for 5 h to obtain a semi-aqueous slurry;

[0064] 4) The semi-aqueous slurry is subjected to solid-liquid separation, the liquid phase is crude acid with a P2O5 mass concentration of 44.8%, and the solid phase is washed and dried to obtain large-particle semi-hydrate gypsum, with a particle size of 40-70 μm.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that in step 2), the sulfate ion concentration in the liquid phase is not monitored in real time, and when the sulfate ion concentration in the liquid phase decreases in the late stage of acid hydrolysis, concentrated sulfuric acid is no longer added to supplement sulfate ions.

[0067] Figure 5 This is a SEM image of the semi-hydrated gypsum prepared in this comparative example. It can be seen from the image that the particle size of the semi-hydrated gypsum is 20-50 μm, indicating that failure to control the sulfate concentration during the acid hydrolysis process will lead to a decrease in particle size.

[0068] Comparative Example 2

[0069] The only difference between this comparative example and Example 1 is that no modifier is added in step 3).

[0070] Figure 6 This is a SEM image of the semi-hydrated gypsum prepared in this comparative example. It can be seen from the image that the particle size of the semi-hydrated gypsum is 5-30 μm, indicating that not adding a modifier during the crystallization process will lead to a decrease in particle size.

[0071] Comparative Example 3

[0072] The only difference between this comparative example and Example 1 is that: in step 2), the sulfate ion concentration in the liquid phase is not monitored in real time, and when the sulfate ion concentration in the liquid phase decreases in the late stage of acid hydrolysis, concentrated sulfuric acid is no longer added to supplement sulfate ions; and no modifier is added in step 3).

[0073] Figure 7 This is a SEM image of the semi-hydrated gypsum prepared in this comparative example. It can be seen from the image that the particle size of the semi-hydrated gypsum is 1-3 μm. Failure to add a modifier and control the sulfate concentration will result in a significant reduction in the particle size.

[0074] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore, characterized in that: The following steps are involved: 1) mixing phosphate rock powder with phosphoric acid, controlling the sulfate ion concentration in the liquid phase to be 1-2%, and pre-dissolving at a temperature of 80-85° C. to obtain a pre-dissolved slurry; the particle size of the phosphate rock powder is ≤100 mesh, the P2O5 content of the phosphate rock powder is 28.5-30%, the MgO content is 1-2%, and the total content of Fe2O3 and Al2O3 is 3-5%; 2) adding phosphate rock powder to the pre-dissolved slurry, controlling the sulfate ion concentration in the liquid phase to 2-5%, and performing acid hydrolysis at a temperature of 85-90° C. to obtain an acid hydrolysis slurry; 3) adding a modifier to the acid hydrolysis slurry, and then adding concentrated sulfuric acid, controlling the sulfate ion concentration in the liquid phase to be 4-10%, and performing crystallization at a temperature of 85-90° C. to obtain a semi-aqueous slurry; the modifier is one or more of N-ethylacetamide and acrylamide, and the concentration of the modifier in the acid hydrolysis slurry is 40-160 ppm; 4) The semi-aqueous slurry is subjected to solid-liquid separation, the liquid phase is crude acid, and the solid phase is washed and dried to obtain large-particle semi-hydrated gypsum, wherein the particle size of the large-particle semi-hydrated gypsum is 40-80 μm.

2. The method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore according to claim 1, characterized in that: The mass concentration of the phosphoric acid is 33-38% in terms of P2O5.

3. The method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore according to claim 1, characterized in that: The mass ratio of the phosphate rock powder added in step 1) to the phosphoric acid is 1:(20-30), and the mass ratio of the phosphate rock powder added in step 2) to the phosphoric acid is 1:(2.5-4).

4. The method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore according to claim 1, characterized in that: The pre-dissolution time is 0.5-1h, the acid hydrolysis time is 3-5h, and the crystallization time is 3-5h.

5. The method for preparing large-particle hemihydrate gypsum by acid hydrolysis of high-impurity phosphate ore according to claim 1, characterized in that: The mass concentration of P2O5 in the crude acid is 40-45%.

Citation Information

Patent Citations

  • Method for producing alpha-semi-hydrated gypsum through wet-process phosphorus processing

    CN113148968A

  • Method for controlling coarse crystallization of semi-hydrated gypsum

    CN113185160A